Crime Prevention as an Approach to Urban Security Enhancement - Paraušić, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
Urban crime is one of the traditional themes in criminology, and the contemporary research on this phenomenon is connected with the concept of urban security. From this perspective, urban crime could be seen as a security threat, and crime prevention as one of the models, policies or security measures that security providers implement to achieve security in the city. This paper aims at addressing the main features of crime prevention in the cities, which is in the function of improving urban security. In the first part of the paper, some theoretical assumptions on which the modern study of urban crime prevention is based are reviewed. Then, certain models, strategies and policies for crime prevention in the cities based on the rich research practice in this area are presented. Finally, some recommendations are given for adequate planning of crime prevention programs that could contribute to the overall enhancement of urban security.